Methodical recommendations for preparation and defence of a coursework for 6th year student of medico-psychological faculty - Chaban, Олег; Khaustova, Олена; Trachuk, Лідія; Bezsheiko, Віталій (Psychosomatic Medicine and General Practice, 2017)
The methodical recommendations are devoted to the peculiarities of the writing of the coursework, its design according to requirements, preparation for defense, and aimed at helping students more effectively organize their own work and conduct their own research. The coursework is carried out by students of the 6th year of the medical-psychological faculty during the study of the discipline "Psychotherapy", in accordance with the requirements approved by the Department of Psychosomatic Medicine and Psychotherapy. Methodological recommendations consist of four sections: how to write a coursework; how to arrange coursework; how to defend coursework; general rules and requirements for publications, and also contain a list of sources and applications used.